1993
DOI: 10.1017/s0022149x00012967
|View full text |Cite
|
Sign up to set email alerts
|

Imported Opisthorchis viverrini and parasite infections from Thai labourers in Taiwan

Abstract: In order to determine the prevalence of intestinal parasites among labourers from Thailand in Taiwan, the stool samples from 1364 Thai labourers were examined by the formalin-ether concentration method and 18·0% were found to be infected with one or more parasites. The infection rates of hookworm, Opisthorchis viverrini, Strongyloides stercoralis, Enterobius vermicularis, Ascaris lumbricoides, Hymenolepis nana, Capillaria philippinensis, Schistosoma japonicum, Echinostoma sp., Entamoeba coli, Giardia lamblia, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 8 publications
1
19
1
Order By: Relevance
“…However, this method is usually not employed in large-scale epidemiological studies or screening examinations. The negative findings obtained in the previous studies (Peng et al 1993;Wang 1998;Fan et al 1999) may be due to this technical problem. Although the formalin-ethyl acetate sedimentation technique is not very suitable for the detection of this parasite, we found a high prevalence of 3.4% among laborers.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…However, this method is usually not employed in large-scale epidemiological studies or screening examinations. The negative findings obtained in the previous studies (Peng et al 1993;Wang 1998;Fan et al 1999) may be due to this technical problem. Although the formalin-ethyl acetate sedimentation technique is not very suitable for the detection of this parasite, we found a high prevalence of 3.4% among laborers.…”
Section: Discussionmentioning
confidence: 48%
“…In the early 1990s, 18% of Thai laborers in North Taiwan were reported to harbor one or more species of intestinal parasite (Peng et al 1993). However, the prevalence among Southeast Asian laborers in North Taiwan decreased from 33.3% in 1992-1993 to 4.6% in 1995-1996.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 In developed countries, the disease has become more prevalent with the influx of immigrants from Asia. [4][5][6] Humans are infected by eating raw or semi-cooked cyprinoid fishes harboring the O. viverrini infective stage called metacercariae. General symptoms include dyspepsia, fatigue, and upper quadrant abdominal pain.…”
Section: Introductionmentioning
confidence: 99%
“…The population was divided according to the presence and intensity of infection as follows, 33% were uninfected, 59% had light infections (less than 1000 eggs per g of faeces; EPG), 7% had moderate infections (1000-10 000 EPG), and 1% had heavy (greater than 10 000 EPG) [28] . Therafter, Peng et al [29] have been reported that all 1364 Thai labourers in Taiwan were examined for stool samples and 18.0% were found to be infected, with O. viverrini at 7.0%. The prevalence was highest among the 21-25 age group (24.8%).…”
Section: Thailandmentioning
confidence: 99%